Collective and individual memories:narrations about the transformations in the Nenets society - Laptander, Roza (Arctic Anthropology, 2017)
The Tundra Nenets have a very well developed oral history tradition, and they use different ways to disseminate this knowledge and memories. This paper examines Nenets’ oral history within the transformation of collective and personal memories about early collectivization in the tundra under the Soviet regime. The Nenets are a flexible society and accommodated most of the external changes in their life without abandoning their nomadic life with reindeer on the tundra. However, even though Nenets elders speak quite positively about the time of Soviet collectivization, relocation, and industrialization in their homeland, it seems that they constantly try to conceal all negative memories and stories connected to tragic events of that time. In place of these memories, they create positive stories to tell young people that selectively edit out the negatives of the past. (This paper is part of a series of publications focusing on Arctic Oral History. The series is one outcome of the Finnish Academy Project ORHELIA (Oral History of Empires by Elders in the Arctic), decision number 251111).